Caracterização zoométrica e genética de ovinos Morada Nova. - Silva, Regina Cely Benício da (2012)
The aim of the present study was to offer a phenotypic and genetic characterization of herds of the Morada Nova breed of sheep in four states in northeastern Brazil through zoometric measures and an analysis of 23 microsatellite markers. Collections were performed among 33 herds in semi-arid regions of the states of Ceará, Rio Grande do Norte, Paraíba and Pernambuco. Twenty adult sheep were analyzed on each property. Fourteen zoometric measures were performed for the characterization of the morphostructural pattern of the herds. Moreover, fleece samples were collected for the genetic analysis of 470 animals: 198 from the state of Ceará (14 populations), 118 from Paraíba (7 populations), 45 from Pernambuco (3 populations) and 109 from Rio Grande do Norte (8 populations). The results of the zoometric study demonstrate the formation of subgroups of the Morada Nova breed in northeastern Brazil and the genetic study suggests sub-structuring of the populations, with genetic variability both between and within populations. Genetic variability was greater between populations. The RNG herd located in the state of Rio Grande do Norte is genetically distant from the other populations of Morada Nova sheep, making it the reference herd for the conservation of the breed as well as for future studies on genetic diversity. The varieties of Morada Nova with reddish fleece are genetically distant from those with white fleece. Further studies are needed for a more detailed evaluation.